Haploidentical hematopoietic stem cell transplantation in adults with Philadelphia‐negative acute lymphoblastic leukemia: No difference in the high‐ and low‐risk groups. Issue 7 (2nd September 2014) - Mo, Xiao‐Dong; Xu, Lan‐Ping; Zhang, Xiao‐Hui; Liu, Dai‐Hong; Wang, Yu; Chen, Huan; Yan, Chen‐Hua; Chen, Yu‐Hong; Han, Wei; Wang, Feng‐Rong; Wang, Jing‐Zhi; Liu, Kai‐Yan; et al.
<x xml:space="preserve">Abstract</x> Allogeneic hematopoietic stem cell transplantation (HSCT) is the most effective post‐consolidation therapy and curative option for adult patients with Philadelphia chromosome‐negative (Ph‐negative) acute lymphoblastic leukemia (ALL) in first complete remission (CR1). A human leukocyte antigen (HLA)‐haploidentical related donor (haplo‐RD) is one of the most important alternative sources for those without HLA‐identical sibling donor (ISD). The present study aimed to evaluate the outcomes of haploidentical hematopoietic stem cell transplantation (haplo‐HSCT) in adult Ph‐negative ALL CR1 patients (n = 183). We produced an unmanipulated haplo‐HSCT protocol including granulocyte colony stimulating factor (G‐CSF) for all donors, intensive immune suppression, anti‐thymocyte globulin, and combination of G‐CSF‐primed bone marrow harvest and G‐CSF‐mobilized peripheral blood stem cells harvest as the source of stem cell grafts. The median age for high‐risk versus low‐risk groups were 29 versus 23 years. Three‐year incidences of relapse mortality and nonrelapse mortality for high‐risk versus low‐risk groups were 7.1% versus 11.1% (p = 0.498) and 18.0% versus 16.2% (p = 0.717), respectively. Three‐year probabilities of disease‐free survival and overall survival for high‐risk versus low‐risk groups were 67.6% versus 68.2% (p = 0.896) and 74.9% versus 72.7% (p = 0.981), respectively. Multivariate analysis showed that limited cGVHD and a lower pre‐HSCT comorbidity burden were associated with better outcomes. In summary, comparable outcomes were observed among high‐ and low‐risk Ph‐negative ALL CR1 patients after haplo‐HSCT. Haplo‐RD could be considered for adults with Ph‐negative ALL in CR1 as an important alternative source of donors in cases when no ISD is available.